2012
DOI: 10.1177/0194599812437534
|View full text |Cite
|
Sign up to set email alerts
|

Cost Considerations in the Treatment of Oropharyngeal Squamous Cell Carcinoma

Abstract: An algorithm of transoral surgical treatment of OP SCCA with adjuvant treatment as indicated by pathology is more cost conscious than an algorithm of treatment of all OP SCCA with CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 21 publications
1
45
2
Order By: Relevance
“…With the advent of de-intensification clinical trial results showing similar, if not superior, overall survival rates in HPV-positive compared to HPV-negative HNSCCs [23,35,36], while having fewer and/or milder side-effects, instating an HPV testing protocol can be beneficial. Furthermore, although the majority of respondents in our survey who did not perform any HPV testing did not do so due to the high costs of the tests, a recent study by Moore et al demonstrated a significant reduction in treatment costs if de-intensification is to be undertaken in HPV-positive HNSCC patients [37]. However, for the time being, no change should be performed in the standard treatment based solely on HPV status, as there are no official guidelines and a holistic understanding of the disease has yet to be reached.…”
Section: Discussionmentioning
confidence: 81%
“…With the advent of de-intensification clinical trial results showing similar, if not superior, overall survival rates in HPV-positive compared to HPV-negative HNSCCs [23,35,36], while having fewer and/or milder side-effects, instating an HPV testing protocol can be beneficial. Furthermore, although the majority of respondents in our survey who did not perform any HPV testing did not do so due to the high costs of the tests, a recent study by Moore et al demonstrated a significant reduction in treatment costs if de-intensification is to be undertaken in HPV-positive HNSCC patients [37]. However, for the time being, no change should be performed in the standard treatment based solely on HPV status, as there are no official guidelines and a holistic understanding of the disease has yet to be reached.…”
Section: Discussionmentioning
confidence: 81%
“…14 Defining cost as reimbursement during a 3-month window of treatment, they concluded that upfront surgery with adjuvant treatment decided by findings on histopathology was more cost conscious. 14 However, they did not have patients treated with radiation-alone or radiation followed by surgery.…”
Section: Discussionmentioning
confidence: 99%
“…14 Defining cost as reimbursement during a 3-month window of treatment, they concluded that upfront surgery with adjuvant treatment decided by findings on histopathology was more cost conscious. 14 However, they did not have patients treated with radiation-alone or radiation followed by surgery. In addition, their surgical approaches included both transoral endoscopy with laser microsurgery and transoral robotic surgery; the latter is generally billed as an un-coded charge such that reimbursement may not reflect the cost to the institution, which would absorb potential losses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations